N = 1: initial impressions of systemism in Canadian foreign policy. Issue 3 (2nd September 2021) - Lane, Andrea
ABSTRACT: Systemism as a method for the study of Canadian foreign defence policy offers an opportunity for fruitful collaboration across theoretical and methodological subdivisions in the field. In particular, the approach could provide an excellent method through which to showcase feminist causal logic for a more mainstream audience, which tends to view feminist scholarship as being far removed from its concerns and policy-relevant Canadian foreign policy. This review offers a somewhat idiosyncratic assessment of the strengths and weaknesses of systemism as presented in this special issue of CFPJ. I discuss how I see myself using sytemism as a writing and teaching tool in the future.